Association between dietary patterns and chronic kidney disease in elderly patients with type 2 diabetes: a community-based cross-sectional study - Ling Cao; Peng Yu; Lei Zhang; Qiuming Yao; Fang Zhou; Xiaoying Li; Xiaomu Li (Nutrition Journal)
Abstract Background Chronic kidney disease (CKD) is prevalent among elderly patients with type 2 diabetes mellitus (T2DM). The association between dietary patterns and CKD in elderly T2DM patients remains understudied. This study aimed to investigate the relationship between dietary patterns and CKD in elderly Chinese patients with T2DM. Methods This community-based cross-sectional study included 5,713 elderly T2DM patients (aged ≥ 65 years) from Xiangcheng District, Suzhou, China. Dietary intake was assessed using a validated food frequency questionnaire, and dietary patterns were identified using factor analysis. Each participant was assigned a score for each identified dietary pattern, with higher scores indicating a greater alignment of their diet with the respective pattern. Quartiles of these pattern scores were utilized as the primary exposures in the analysis. CKD was defined as albuminuria, reduced estimated glomerular filtration rate (eGFR), or both. Logistic regression models assessed CKD prevalence across quartiles of dietary pattern scores, expressed as adjusted odds ratios (ORs) with 95% confidence intervals (CIs). Results CKD prevalence was 45.7%. Four dietary patterns were identified: “traditional southern”, “high-protein”, “balanced” and “imbalanced”. A balanced dietary pattern, featured with high intake of fruits, dairy products, eggs, snacks, crab and shellfish, and fish and shrimp, was associated with lower CKD prevalence. The adjusted ORs for CKD across ascending quartiles were 0.99 (95% CI: 0.85–1.16), 0.89 (95% CI: 0.76–1.04), and 0.73 (95% CI: 0.62–0.86). The imbalanced dietary pattern, characterized by high intake of green leafy vegetables, refined grains, and red meat but low dietary diversity, was associated with increased CKD prevalence, with ORs of 1.01 (95% CI: 0.86–1.18), 1.15 (95% CI: 0.98–1.35), and 1.25 (95% CI: 1.07–1.46) across quartiles. No significant associations were observed for “traditional southern” or “high-protein” dietary patterns. Conclusions Dietary patterns were associated with CKD prevalence in elderly Chinese T2DM patients. A “balanced dietary pattern”, consistent with local dietary customs, was associated with a lower risk of CKD. Further longitudinal and intervention studies are needed to confirm these associations. Graphical Abstract